Growth and Yield Performance of Celery (Apium graveolens L.) Under the Application of Liquid Organic Fertilizer from Tofu Residue in a Wick Hydroponic System - I Made Suryana; Putu Eka Pasmidi Ariati; Luh Putu Yuni Widyastuti; Krecenciana Ketriani Juita (Warmadewa University Press, 2025)
Celery (Apium graveolens L.) originates from Southern Europe and was first described by Carolus Linnaeus in Species Plantarum (1753). In Indonesia, this plant is known as seledri. Celery is an annual herbaceous plant that grows in the form of grass or shrubs. It has an unbranched structure consisting of roots, stems, and leaf stalks. Hydroponic cultivation provides a controlled growth environment, which can optimize plant development. Liquid Organic Fertilizer (LOF) derived from tofu residue contains essential nutrients, namely N (1.2%), P (0.10%), and K (0.12%), which are crucial for plant growth. This study aimed to evaluate the effect of tofu residue-based LOF application and determine the optimum concentration for the growth and yield of celery cultivated using a wick hydroponic system. The research was conducted at BSIP (Agricultural Instrument Standardization Center), Bali. Randomized Completed Block Design (RCBD) was used with six treatment levels: (A1) 100 ml/L water, (A2) 200 ml/L water, (A3) 300 ml/L water, (A4) 400 ml/L water, (A5) 500 ml/L water, and (A6) 600 ml/L water, with four replications, resulting in a total of 24 experimental units. Statistical analysis revealed that the application of tofu residue-based LOF had a highly significant effect on all observed parameters. The results showed that the 400 ml/L water treatment produced the best outcomes, with a fresh plant weight of 14.18 g and an oven-dry weight of 1.78 g.